2013
DOI: 10.1007/978-3-7091-1511-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between Ceramide and Redox Signaling: Implications for Endothelial Dysfunction and Renal Disease

Abstract: Recent studies have demonstrated that cross talk between ceramide and redox signaling modulates various cell activities and functions and contributes to the development of cardiovascular diseases and renal dysfunctions. Ceramide triggers the generation of reactive oxygen species (ROS) and increases oxidative stress in many mammalian cells and animal models. On the other hand, inhibition of ROS-generating enzymes or treatment of antioxidants impairs sphingomyelinase activation and ceramide production. As a mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 141 publications
2
39
0
Order By: Relevance
“…In the case of further downstream mechanisms, our work focused on ASM, one of the common responding molecules of various pathologic stimuli, which mediates hepatocytic damage by triggering endoplastic reticulum stress, autophagic disorder, lysosomal membrane permeabilization, oxidative stress and apoptosis. Acid sphingomyelinase is involved in liver disorders such as insulin resistance (I/R), lipogenesis, fibrosis and steatosis . We found that 5 days noise exposure raised ASM expression significantly which contributes to noticeable Cer accrual in hepatocytes.…”
Section: Discussionmentioning
confidence: 90%
“…In the case of further downstream mechanisms, our work focused on ASM, one of the common responding molecules of various pathologic stimuli, which mediates hepatocytic damage by triggering endoplastic reticulum stress, autophagic disorder, lysosomal membrane permeabilization, oxidative stress and apoptosis. Acid sphingomyelinase is involved in liver disorders such as insulin resistance (I/R), lipogenesis, fibrosis and steatosis . We found that 5 days noise exposure raised ASM expression significantly which contributes to noticeable Cer accrual in hepatocytes.…”
Section: Discussionmentioning
confidence: 90%
“…An oxidizing effect of naphthazarin has been shown previously [40,41]. In a wide variety of nucleated cells, ceramide triggers oxidative stress, which in turn favours sphingomyelinase activation and ceramide production [42]. Whether or not the interplay between oxidative stress and ceramide formation is similarly effective in erythrocytes remains to be shown.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of NADPH oxidase subunits or cofactors and antioxidant enzymes in lipid rafts (Li & Zhang, 2013) suggests that lipid rafts play an important role in the regulation of these enzymes. In addition, alteration of lipid rafts was suggested to occur in CerS2 null mice (Park et al ., 2013), and the function of lipid rafts is altered with aging (Fulop et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes are present in lipid rafts on cell membranes or have close relationships with lipid rafts (Li & Zhang, 2013). In addition, redox molecules, such as the NADPH oxidase subunits or cofactors, are present in lipid rafts (Li & Zhang, 2013). This evidence supports the view that lipid rafts are involved in initiating and transmitting redox signaling in cells.…”
Section: Introductionmentioning
confidence: 99%